A first-order BSPDE for swing option pricing - Bender, C.; Dokuchaev, Nikolai (John Wiley & Sons, 2014)
We study an optimal control problem related to swing option pricing in a general non-Markovian setting in continuous time. As a main result we uniquely characterize the value process in terms of a first-order nonlinear backward stochastic partial differential equation and a differential inclusion. Based on this result we also determine the set of optimal controls and derive a dual minimization problem.